EXPORT-ORIENTED STRATEGY OF DEVELOPMENT MAKING IN THE MANAGEMENT OF INDUSTRIAL ENTERPRISES’ PROFITABLE ACTIVITY - SAVITSKYI АNDRII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The essence of separate elements of export-oriented strategy of development making in management of profitable activity of industrial enterprises has been researched. The main tendencies of foreign economic activity of national enterprises under the conditions of integration processes have been underlined. The role of macroeconomic and regional institutions that deals with foreign trade activity of industrial enterprises has been studied. The main possibilities that are given for national manufactures with integration processes in the sphere of export activity have been formed. Aspects of extensive and intensive growth of industrial enterprises on the basis of strengthening their export orientation have been characterized. The essence of export-oriented strategy of development from the basic scientific views has been researched. The connection between export-oriented strategy of development and profitability has been actualized. The meaning of transformation changes of economy under the influence of integration stages through the activity of industrial enterprises and its export-oriented strategy making have been detailed. The dependence of economic conditions of integration cycles, complexity of levels of export-oriented strategy of development and management of enterprise’s profitable activity has been emphasized. There were proposed macro- and micro-levels of management that are aimed to study demands of external environment and implement its aspects to the operating and manufacturing activity of export-oriented enterprises’ performance. The importance of macro- and micro-levels of management for starting the process of making export-oriented strategy of development in order to increase the enterprise’s profitability has been detailed and presented in structure that provided and intensified by direct and returned feedback.